Health-related quality of life in children with traumatic brain injury; relationship between parent–proxy report and child self-report. (29th September 2015) - Hameed, B; Miller, H; Curran, A; Penn, A; McCarter, R; Sharples, P
Abstract : Introduction: The ultimate aim of neurorehabilitation for traumatic brain injury (TBI) survivors is good health-related quality of life (HRQL). Despite recommendation by the WHO that self-reporting measures of HRQL in children should be used whenever possible, paediatric TBI studies have almost all have used parent–proxy report to assess HRQL. Aims: (1) To examine the relationship between parent and child-report estimations of HRQL at 1 (T1), 6 (T6) and 12 (T12) months post-TBI; (2) to investigate factors influencing parent–child agreement. Methods: Prospective cohort study. HRQL was measured by Paediatric Quality of Life Inventory (PedsQL). Severity of TBI was classified by admission Glasgow Coma Score (GCS), post-traumatic amnesia (PTA) and length of hospital stay (LOS). Verbal and performance IQ in the child were assessed by the Wechsler Intelligence Scale for Children-III; emotional state by the Child Behaviour Checklist (CBCL). Burden to the main carer and family were assessed by Beck Depression Inventory (BDI) and family burden of injury inventory (FBII). Results: 47 TBI subjects were studied. Mean age was 11.2 yrs. 66% were boys. 51% had severe/moderate TBI, 49% mild. Significant correlations were found between parent and child report PedsQL total, physical and psychosocial summary scores at T1 (TSS, r=0.36, p=0.020; physical, r<0.001; PSS, r=0.32, p=0.036), T6 (TSS, r=0.63, p<0.001; physical, r=0.69, p<0.001; PSS, r=0.58, p<0.001) and T12 (r=0.57, p=0.001; physical, r=0.74, p<0.001; PSS, r=0.45, p=0.008) post-TBI. In contrast to other chronic disorders, parents tended to score HRQL higher than children. However, mean differences between parent and child scores were not significant for any domain at any time point, with the exception of school domain at T6 (mean bias, −7.91, SD=21.88, p=0.022) and T12 (mean bias, −7.83, SD=19.55, p=0.036). Differences between parent and child-report scores did not correlate with VIQ or PIQ, but did significantly correlate with parent and child emotional state at T1 and T6 (T6, BDI, r=−0.40, p=0.010; FBII, r=−0.56, p=0.001; CBCL total problem score, r=−0.511, p=0.001). By T12, differences only correlated with injury severity (admission GCS, r=0.44, p=0.011; PTA, r=−0.51, p=0.009; LOS, r=−0.49, p=0.008). Conclusion: Parent and child-report HRQL generally agree, despite emotional state influencing assessment. Parents tend to underestimate HRQL after TBI.